Benchmarking to trigger and sustain the introduction of cleaner production in small to medium sized enterprises - Altham, William Ashley (Curtin University, 2003)
This thesis investigates benchmarking (and associated capacity building activities) as a trigger for the diffusion and implementation of Cleaner Production. The critical success factors for the environmental benchmarking process are: The identification of gaps in environmental performance in areas important to the long-term future of the businesses; Providing and/or promoting the drivers to close the performance gaps; Ensuring business managers possess the ability and tools to close the performance gap. A program was developed implementing these factors and delivered to the drycleaning industry in Western Australia. This program identified large performance gaps for the different Eco-Efficiency indicators. The participants accepted the benchmarks (which are amended for 'economies of scale' if required) as suitable targets and committed their businesses to achieving these in their action plans. Economic benefits, managing environmental risk and maintaining their licence to operate were found to be important drivers. Participants on average reduced hazardous waste generation by 48%, improved their chemical efficiency by 30% and their energy efficiency by 9%, while individual business manager's levels of Eco-Efficiency improvements varied widely. The businesses with the higher levels of productivity and the greatest experience in the industry obtained the greatest improvements in Eco-Efficiency from the program. Furthermore, the business managers involved in the program had a significantly higher uptake of Cleaner Production in comparison with control groups, both inside the drycleaning sector as well as in 3 other sectors dominated by small to medium-sized enterprises.This research indicates that benchmarking for small businesses needs to be part of an on-going industry specific capacity building program with the opportunity to network in a supportive atmosphere. When this is the case, improved environmental accounting practices and benchmarking can trigger and sustain the uptake of Cleaner Production to improve the Eco-Efficiency of small businesses.